Possible enhancement of antioxidative activities in medicinal in herbal plant through nitrogen fertilization. - Jaafar, Hawa ZE
An experiment was designed to characterize the relationship among gluthatione (OSH) production, oxidized gluthatione (OSSG), total flavonoid, anthocyanin, ascorbic acid and antioxidant activities (FRAP, DPPH) in three varieties of Labjsja pumila Blume (var. alata,pumila, lanceolata) under four nitrogen fertilization levels (0, 90, 180,270 kg N/ha). Nitrogen (N) fertilization imposed acute impact on the production of GSH and GSSG, anthocyanin, total flavonoid and ascorbic acid that increased steadily with decreasing N level from 270 to 0 kg N/ha. Neither varietal nor its interaction with N level being observed. At the highest N level, L. pumila exhibited significantly lower antioxidant activities than those exposed to limited N-growing condition. Significant positive correlations were obtained among antioxidant activities, total flavonoid, GSH, GSSG, anthocyanin and ascorbic acid suggesting an increase in antioxidative activities in L. pumila under low N fertilization could be attributed to high contents of these compounds. It could also be concluded that the quality of L. pumila could be enhanced with manipulation of N fertilization, and that excessive N application should be avoided to ensure high herbal quality.